Spin-glass magnetic ordering in CoMgGaO2BO3 ludwigite - Ivanova, N.B.; Platunov, M.S.; Knyazev, Yu.V.; Kazak, N.V.; Bezmaternykh, L.N.; Eremin, E.V.; Vasiliev, A.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The single crystal needle shape samples of diamagnetically diluted cobalt ludwigite CoMgGaO2BO3 have been grown by the flux method. The results of x-ray diffraction and both dc and ac magnetic measurements are presented. The unit cell volume undergoes a noticable growth under dilution from 328.31 Å3 for the parent compound Co3O2BO3 to 345.46 Å3 for CoMgGaO2BO3. The temperature of magnetic transition is considerably lower for the latter compound (25 K against 43 K for Co3O2BO3). The dc magnetization temperature dependencies undergo the splitting of field cooled and zero-field cooled regimes and the ac magnetic susceptibility temperature dependencies are frequency dependent pointing out a possible spin-glass freezing in the magnetic system.